From Intramolecular (Circular) in an Isolated Molecule to Intermolecular Hole Delocalization in a Two‐Dimensional Solid‐State Assembly: The Case of Pillarene. Issue 8 (1st February 2018) - Ivanov, Maxim V.; Wang, Denan; Navale, Tushar S.; Lindeman, Sergey V.; Rathore, Rajendra
Abstract: To achieve long‐range charge transport/separation and, in turn, bolster the efficiency of modern photovoltaic devices, new molecular scaffolds are needed that can self‐assemble in two‐dimensional (2D) arrays while maintaining both intra‐ and intermolecular electronic coupling. In an isolated molecule of pillarene, a single hole delocalizes intramolecularly via hopping amongst the circularly arrayed hydroquinone ether rings. The crystallization of pillarene cation radical produces a 2D self‐assembly with three intermolecular dimeric (sandwich‐like) contacts. Surprisingly, each pillarene in the crystal lattice bears a fractional formal charge of +1.5. This unusual stoichiometry of oxidized pillarene in crystals arises from effective charge distribution within the 2D array via an interplay of intra‐ and intermolecular electronic couplings. This important finding is expected to help advance the rational design of efficient solid‐state materials for long‐range charge transfer. Abstract : Solid‐state assembly with a fractional charge : Crystallization of the pillar[5]arene cation radical produces a 2D self‐assembly with three intermolecular dimeric (sandwich‐like) contacts, where each pillarene in the crystal lattice surprisingly bears a fractional formal charge of +1.5.